Photocatalytic zinc oxide on flexible polyacrylonitrile nanofibers via sol–gel coaxial electrospinning. Issue 6 (15th April 2020) - Methaapanon, Rungthiwa; Chutchakul, Kanchat; Pavarajarn, Varong
Abstract: Photocatalysts on nanofibers provide a large surface area for high photocatalytic activity, prevent nanoparticle aggregation, and facilitate easy separation from the process fluids. In this work, zinc oxide (ZnO) photocatalysts on flexible polyacrylonitrile (PAN) were prepared via single-step deposition by sol–gel coaxial electrospinning. A core/sheath structure consisting of the PAN polymer covered with a ZnO–polyvinylpyrrolidone (PVP) mixture was fabricated and then calcined at high temperatures to remove the PVP and crystallize the ZnO. The concentrations and viscosities of PAN and PVP were varied to find the appropriate conditions for nanofiber production. The thermal behavior and optimal calcination temperature were investigated via thermogravimetric analysis and Fourier transform infrared spectrometry. ZnO/PAN coaxial nanofibers fabricated using 18% PVP and 12% PAN and calcined at 450 °C in air for 2 h had a ZnO-to-carbon ratio of 0.51. The nanofibers retained their flexibility and exhibited photocatalytic activity toward methylene blue degradation. Graphical abstract: Image 1